STRATEGI PRIORITAS PENINGKATAN EFEKTIVITAS PENGELOLAAN SEKOLAH MENENGAH KEJURUAN BADAN LAYANAN UMUM DAERAH - Arie Wibowo Khurniawan (Jurnal Pendidikan dan Kebudayaan, 2021)
Indonesian government is focusing on improving the quality and effectiveness of Vocational High Schools (SMK) as mandated in Presidential Instruction No. 9 of 2016. One form of its efforts is to transform SMKs into Regional Public Service Bodies (BLUD). This study aims to design a strategy to increase the effectiveness of SMK-BLUD based on the implementation of school governance (SG) and integrated quality management (TQM). This study uses a quantitative approach using the Analytic Hierarchy Process (AHP). Data obtained through the Group Disscusion Forum (FGD) with expert experts. The results of the AHP analysis show that the strategies that can be taken by SMK-BLUDs so that the effectiveness of school management can be implemented maximally is by increasing the implementation of school governance in schools by increasing the criteria for strong and firm leadership in Human Resources (Man) in SMK-BLUD. Meanwhile, based on the results of the analysis of the sub-elements on each element through the ISM, it is considered necessary to improve and improve each sub-element or variable that is at the bottom level first. Then combine the variables at the bottom level with the optimization model that has been analyzed using AHP so that it can improve the performance of variables or sub-elements that are at the bottom level in giving an impact on the variables above it of each element.